Interphase phosphorylation of lamin A - Kochin, Vitaly (The Company of Biologists, 2014)
Nuclear lamins form the major structural elements that comprise the nuclear lamina. Loss of nuclear structural integrity has been implicated as a key factor in the lamin A/C gene mutations that cause laminopathies, whereas the normal regulation of lamin A assembly and organization in interphase cells is still undefined. We assumed phosphorylation to be a major determinant, identifying 20 prime interphase phosphorylation sites, of which eight were high-turnover sites. We examined the roles of these latter sites by site-directed mutagenesis, followed by detailed microscopic analysis – including fluorescence recovery after photobleaching, fluorescence correlation spectroscopy and nuclear extraction techniques. The results reveal three phosphorylation regions, each with dominant sites, together controlling lamin A structure and dynamics. Interestingly, two of these interphase sites are hyper-phosphorylated in mitotic cells and one of these sites is within the sequence that is missing in progerin of the Hutchinson-Gilford progeria syndrome. We present a model where different phosphorylation combinations yield markedly different effects on the assembly, subunit turnover and the mobility of lamin A between, and within, the lamina, the nucleoplasm and the cytoplasm of interphase cells.